Linux kernel programming. create user-kernel interfaces, work with peripheral I/O, and handle hardware interrupts /: create user-kernel interfaces, work with peripheral I/O, and handle hardware interrupts. Char device drivers and kernel synchronization : Part 2, (2021) - Billimoria, Kaiwan N
No abstract available